Effect of anticoagulants on the risk of delayed bleeding after colorectal endoscopic submucosal dissection - Ogiyama, Hideharu; Inoue, Takuya; Maekawa, Akira; Yoshii, Shunsuke; Yamaguchi, Shinjiro; Nagai, Kengo; Yamamoto, Masashi; Egawa, Satoshi; Horimoto, Masayoshi; Ogawa, Hiroyuki; Nishihara, Akihiro; Komori, Masato; Kizu, Takashi; Tsutsui, Shusaku; Tsujii, Yoshiki; Hayashi, Yoshito; Iijima, Hideki; Takehara, Tetsuo (Endoscopy International Open, 2020)
Background and study aims In patients receiving antithrombotic therapy, the risks of delayed bleeding after endoscopic procedures for gastrointestinal neoplasms become a major problem. Few reports have shown the effects of delayed bleeding in patients taking anticoagulants after colorectal endoscopic submucosal dissection (ESD). This study aimed to evaluate the delayed bleeding events after colorectal ESD in patients receiving anticoagulant therapy.Patients and methods We retrospectively analyzed 87 patients taking anticoagulants who underwent colorectal ESD from April 2012 to December 2017 at 13 Japanese institutions participating in the Osaka Gut Forum. Among these patients, warfarin users were managed with heparin bridge therapy (HBT), continued use of warfarin, a temporary switch to direct oral anticoagulation (DOAC), or withdrawal of warfarin, and DOAC users were managed with DOAC discontinuation with or without HBT. We investigated the occurrence rate of delayed bleeding and compared the rates between warfarin and DOAC users.Results The delayed bleeding rate was 17.2 % among all patients. The delayed bleeding rate was higher in DOAC users than in warfarin users (23.3 % vs. 11.4 %, P = 0.14), although no statistically significant difference was observed. In DOAC users, the delayed bleeding rates for dabigatran, rivaroxaban, apixaban, and edoxaban users appeared similar (30 %, 18.2 %, 22.2 %, and 25 %, respectively). The onset of delayed bleeding in both warfarin and DOAC users was late, averaging 6.9 and 9.4 days, respectively.Conclusions Among patients taking anticoagulants, the risk of delayed bleeding after colorectal ESD was relatively high and the onset of delayed bleeding was late.